Effect of silanecoupling agent on properties of biocomposites based on poly(lactic acid)and durian rind cellulose - Penjumras, Patpen; Abdul Rahman, Russly; A. Talib, Rosnita; Abdan, Khalina (1757-8981; ESSN: 1757-899X, 2016)
Durian rind cellulose reinforced poly(lactic acid) (PLA) biocomposites were prepared using Brabender internal mixer followed by hot compression molding technique. Cellulose was previously treated by 3-aminopropyltriethoxysilane for improving the compatibility with PLA matrix. The silane-grafting of cellulose was confirmed via Fourier transform infrared spectroscopy (FTIR) with the presence of Si-O-Si, Si-C, and Si-O-C bonds. The silane-treated cellulose was subsequently introduced into PLA matrix, and the effects of cellulose surface modification on mechanical, thermal and morphological properties, and water absorption of biocomposites were studied. It was found that silane-treated cellulose reinforced biocompositeshave superior mechanical properties compared with untreated cellulose reinforced biocomposites. The lowest crystallization temperature of silane-treated biocomposites was confirmed via Differential scanning calorimetry (DSC). Scanning electron microscopy (SEM) investigation also showed that adhesion of cellulose and PLA matrix was improved by modification of cellulosesurfaceusing3-aminopropyltriethoxysilanewhich can result in less water absorption into biocomposites.